Analysis of Quality of Life in Patients after Surgical Correction of Ascending Aortic Pathology Using Minimally Invasive Access - Vayda, V. V.; Kravchenko, V. I.; Zhekov, I. I.; Kravchenko, I. M. (Ukrainian Journal of Cardiovascular Surgery, 2020)
The assessment of quality of life-associated health is an important factor in determining the severity of the condition and the strategy for choosing surgical access in the treatment of patients with ascending aorta pathology. Introduction. Given that the use of minimally invasive access in the correction of aortic valve disease in combination with ascending aortic pathology accelerates the functional recovery of patients, reduces patient’s stay in hospital, this issue requires careful approach and the only correct choice of treatment method. Aim. To evaluate the quality of life of patients using post-operative SF-36 general medical questionnaire after surgical correction of ascending aorta pathology through J-shaped upper ministernotomy compared with traditional access. Materials and methods. In the SI “National Amosov Institute of Cardiovascular Surgery of the NAMS of Ukraine” from 2016 to 2019 we analyzed the data of 126 patients with ascending aorta pathology. All patients were divided into two groups, depending on the choice of surgical access. Patients were sequentially examined and selected for surgical correction of ascending aorta pathology. Conclusions. Our study has proved that the use of minimally invasive access improves the quality of life of patients in the postoperative period and is safe for patients.